(untitled) (Journal of Advanced Research in Social Sciences, 2019)
This research aims to examine gender differences in parents’ expectations for the education of their children in China. With rich information from the 2013/14 wave of China Education Panel Survey Data, this study used the ordinary least squares regression with the statistical package STATA to examine the effects of teenager gender, the number of siblings and sibling sex composition on parents’ educational expectations in China. Different from previous studies in China, this study found that parents have higher educational expectations for girls than for boys, and the higher rate of return to education for girls might be one of the explanations for this phenomenon. Additionally, residential areas, parents’ educational levels, and father’s occupational status show a significant impact on narrowing the gender gap in parents’ educational expectations. This study also focuses on the sibling composition in the family, which includes the number of siblings and the sibling sex composition. Consistent with the dilution model, a larger number of siblings has a negative impact on parents’ educational expectations, but this impact has no gender differences. Besides, due to the previous family planning policy, a large number of Chinese families only have one child. This study found that in both one-child families and multiple-children families, parents still have higher educational expectations for girls, and even in multiple-children families this preference for girls to receive more education is more significant. Different as expected, sibling sex composition does not show any statistically significant influence on parents’ educational expectations.